ABNORMAL GLUCOSE TOLERANCE AND THE FETO-MATERNAL OUTCOME - Kaluarachchi, A; DeAlwis, D; Gnanasekeream, R; Gunawdnsa, N; Wijeratne, C N; Seneviratne, H R (My University, 2001)
Objective: To determine the maternal/ fetal outcome of abnormal glucose tolerance in pregnancy. Setting : The University Obstetric Unit, De Soysa Hospital for Women, Colombo. Design : A retrospective descriptive study. Method: From July 1998 to November 2000, abnormal glucose tolerance was detected in 220 pregnant women. Among them, 24 had established diabetes mellitus and were excluded from the study. The remaining 196 were free of previous abnormal glucose tolerance and their records were analyzed to determine the relationship of blood sugar control and maternal/ fetal complications. Results : Blood sugar control on diet was adequate in 78.06%(n=153) subjects, while insulin was also required by 21.94%(n=43). Pregnancy induced hypertension appeared in 15.03%(n=23) of the diet controlled group and 13.95%(n=6) in the insulin controlled group. Polyhydramnios was seen among 3.27%(n=5) in the diet controlled group and 11.63%(n=5) in the insulin controlled group. The occurrence of intra uterine growth restriction in the diet and insulin controlled groups were I4.38%(n=22) and 23.26%(n=10) respectively. Fetal macrosomia was seen in 21.57%(n=33) of the diet controlled group and 25.58%(n=l 1) in the insulin controlled group. Conclusion: Abnormal glucose tolerance is frequently associated with maternal and fetal complications. These complications appear to occur irrespective of the method of blood sugar control. Therefore vigilant monitoring is recommended even in those with dietary management.
3rd SAFOG Conference, South Asian Federation of Obstetrics and Gyneacology, March 2001